Coupling between evapotranspiration, water use efficiency, and evaporative stress index strengthens after wildfires in New Mexico, USA - Ryan C. Joshi; Annalise Jensen; Madeleine Pascolini-Campbell; Joshua B. Fisher (International Journal of Applied Earth Observations and Geoinformation)
Aim: Examine the effects of evapotranspiration (ET), water use efficiency (WUE), and evaporative stress index (ESI) on wildfire temperature and extent. Compare land cover type proportions in burned area with land cover type proportions in New Mexico. Methods: We used remotely sensed data from NASA’s ECOsystem and Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) to collect ET, WUE, & ESI data. Data were analyzed for burned areas of 10 wildfires that occurred in New Mexico between 2020 and 2022, segmenting the following land cover types: evergreen needleleaf forests, closed shrublands, open shrublands, savannas, woody savannas, grasslands, and other. Results: ET & ESI increased throughout the duration of the wildfires, while WUE decreased. ET vs. WUE were more strongly correlated post-fire (R2 = 0.85) than pre-fire (R2 = 0.20), as was WUE vs. ESI (post-fire, R2 = 0.59; pre-fire, R2 = 0.04). Pre- and post-fire ET and ESI were positively correlated (R2 = 0.61 pre-fire, R2 = 0.53 post-fire), while post-fire WUE was negatively correlated with both post-fire ET (R2 = 0.85) and ESI (R2 = 0.59). We found that the land cover composition of the areas burned by the 10 studied wildfires differs from the land cover composition of New Mexico as a whole (p < 0.05). Conclusions: Our findings present increasing trends in ET and ESI, and decreasing trends in WUE before, during, and after a wildfire. By monitoring changes in those three variables, we can identify areas that are at high risk for wildfires. Savannas and woody savannas should be closely monitored because a disproportionately large proportion of acres burned in 2022 were savannas and woody savannas.